Direct natural gas conversion to value-added chemicals - Hu, Jianli (Chemical engineer) (Boca Raton, FL : CRC Press, 2021)
Direct Natural Gas Conversion to Value-Added Chemicals comprehensively discusses all major aspects of natural gas conversion and introduces a broad spectrum of recent technological developments. Specifically, the book describes heterogeneous and homogeneous catalysis, microwave-assisted conversion, non-thermal plasma conversion, electrochemical conversion, and novel chemical looping conversion approaches. Provides an excellent benchmark resource for the industry and academics Appeals to experienced researchers as well as newcomers to the field, despite the variety of contributing authors and the complexity of the material covered Includes all aspects of direct natural gas conversion: fundamental chemistry, different routes of conversion, catalysts, catalyst deactivation, reaction engineering, novel conversion concepts, thermodynamics, heat and mass transfer issues, system design, and recent research and development Discusses new developments in natural gas conversion and future challenges and opportunities This book is as an excellent resource for advanced students, technology developers, and researchers in chemical engineering, industrial chemistry, and others interested in the conversion of natural gas.
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum chemicals; Gases -- Separation; Natural gas; SCIENCE / Biotechnology; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Chemical & Biochemical